A study on teaching English vocabulary to the 10th grade ethnic minority students at Vung Cao Viet Bac high school through activities. - Nguyễn, Thị Hoàng Yến (University of Languages and International Studies, 2017)
This research was done to investigate the use of learning group activities in teaching English vocabulary to the 10th grade ethnic minority students at Vung Cao Viet Bac high school, Thai Nguyen city, and find out how group activities benefit for both teac (...)